Rezultati štetja vodnih ptic v januarju 2000 v Sloveniji - Štumberger, Borut (Acrocephalus, 2000)
In the waterfowl census carried out in Slovenia on January 15th and 16th 2000 (IWC), 221 observers took part. On the basis of 489 reports, 47,172 aquatic birds were registered in the seven separate count areas. 55 different species were established (Table 1). All water birds were counted. Most important in terms of the birds' numbers were the count areas oF the Drava river, the Slovene Littoral, and the Upper Sava river. The most abundant species during the census was the Mallard Anas platyrhynchos, followed by the Common Coot Fulica atra, Black-headed Gull Larus ridibundus, Great Cormorant Phalacrocoraxcarbo, Yellow-legged Gull Larus cachinnans, Common Gull L. canus,Tufted Duck Aythya fuliguld, Little Grebe Tachybaptus ruficollis and Common Teal Anas crecca. Only standing waters in the interior of the country were more or less frozen over, while in the Littoral and in the Primorska region there was no ice. Partially frozen over were also the large river reservoirs on the Drava and Sava rivers.
Keywords: bird; Birds; ptice; Ecosystem; ornitologija; vodne ptice; Fresh water; Seawater; Slovenia; Slovenija